Anti-thrombotic Effects of CX-397, a Recombinant Hirudin Analog, in a Canine Model of Coronary Artery Thrombosis - Ohyama, Tadashi; Hori, Toshimitsu; Moriike, Mie; Asano, Taiji; Hayashi, Hideya; Iwade, Kazunori; Hosoda, Saichi (Thrombosis and Haemostasis, 1998)
CX-397, a recombinant hirudin analog, is a potent and specific inhibitor of human α-thrombin. We conducted a comparative study of CX-397 and heparin in a canine model of left circumflex (LCX) coronary artery thrombosis to evaluate the anti-thrombotic efficacy of CX-397. Administration of drugs (i. v.; bolus + infusion) was commenced 10 min prior to the initiation of LCX coronary artery electrolytic injury (100 μA for 300 min). All saline-treated control animals (7/7) developed thrombotic occlusion during the experimental period, leaving a residual thrombus mass of 15.4 ± 3.8 mg. Treatment with CX-397 at three incremental dose levels reduced the incidence of occlusion (4/7, 2/5 and 0/7) and decreased thrombus weight (12.6 ± 2.5 mg, 6.3 ± 3.0 mg and 2.1 ± 1.3 mg, respectively) in a dose-dependent manner. At the in termediate dose (15,000 ATU/kg + 15,000 ATU/kg/h) or higher, CX-397 showed significant anti-thrombotic effects (p <0.05 and p <0.01) and suppressed increases in thrombin-antithrombin III complex (TAT) levels (p <0.01 and p <0.001). In the heparin (80 U/kg + 60 U/kg/h)-treated group, the incidence of occlusion (5/7) and thrombus weight (14.1 ± 6.2 mg) did not differ significantly from the control group. Plas ma TAT levels in the heparin group decreased compared with the control group (p <0.01), but was less potent than the intermediate dose CX-397 (p <0.01). The anti-coagulation (activated partial thromboplastin time and activated clotting time) and template bleeding time prolongation effects of heparin were more potent than those of the intermediate dose CX-397 which showed significant anti-thrombotic effects. In conclusion, CX-397 dose-dependently suppressed thrombus formation by inhibition of thrombin activity in a canine coronary artery injury model. The anti-thrombotic efficacy of CX-397 was more potent than that of heparin at equivalent anti-coagulation dosage.